Perceptions of Climate Change and Health Risks Among Urban Older Adults in Mexico City: A Pilot Study - Simone Lucatello; Josafat Francisco Martínez Magaña; Citlali Fernández Vivar; Jorge Orozco Gaytán; Jessica Camacho Ruíz; Lorena Figueroa Escamilla; Mónica Pérez Rodríguez (Atmosphere)
Climate change poses significant risks to public health, particularly for vulnerable populations such as older adults. In Mexico, where extreme weather events are becoming more frequent, understanding how this demographic perceives climate-related health risks is crucial for designing effective adaptation strategies. Limited research exists on this topic; this pilot study aims to assess the perceptions of climate related health risks among older adults from a multidisciplinary team, with data collected at the Centro Médico Nacional “La Raza” in Mexico City. Using a cross-sectional, descriptive, and observational survey design, data were collected from hospitalized and outpatient individuals using a validated instrument that measures perceived environmental and emotional impacts of climate change. Key findings reveal varying levels of awareness and emotional responses to environmental changes, such as heatwaves, droughts, and ecosystem degradation. Participants’ sociodemographic characteristics and existing health conditions are also documented to explore their association with climate risk perceptions. The study highlights the need for tailored health communication strategies and adaptive policies that address the specific vulnerabilities and perceptions of older adults. Results will contribute to building climate-resilient health interventions and support the development of inclusive public health strategies amid global climate change in the country.